Diarrhoea caused by Clostridium difficile in patients with postoperative subhepatic abscess - Stojanović Predrag; Kocić Branislava (Vojnosanitetski Pregled, 2008)
Background. Toxigenic strains of Clostridium difficile in the majority of cases cause disease of the intestinal tract of hospitalized patients. For a long time, Clostridium difficile was considered to produce both types of toxins (A+/B+ strain), however, the investigations conducted in the last ten years point to the existence of clinically significant isolates which produce only toxin B, i.e. toxin A negative / toxin B positive (A-/B+ strain) Clostridium difficile. Case report. We presented the case of a patient admitted to the Surgery Clinic, Clinical Center Nis due to the presence of calculus in the ductus choledochus. Twenty-four hours after the surgical intervention for calculus removal, the first signs of the operative wound infection began to appear. In the course of infection treatment, different antibiotics were administered (cefuroxine, ciprofloxacin, vancomycin, imipenem). After making etiological microbiological diagnosis and application of antibiotics according to antibiogram results, the signs of the operative wound infection began to withdraw, but the patient reported the abdominal pain and liquid stools with traces of blood (up to 17 stools per day). By microbiological examination, Clostridium difficile was cultivated and the presence of toxin B was detected in the stool samples. The patient was sent to the Clinic for Infectious Diseases, where the causal therapy of mitronidazol was administered. Liquid and electrolytes were made up by substitution therapy. After the eight-day-treatment, the patient felt much better, and diarrheas stopped on the 10th day of the therapy application. Conclusion. Our results have shown that toxingen strains Clostridium difficile are present in our country so this bacterium sort have to be considered in differential causal diagnosis of diarrhoea syndrom. Considering that it can cause difficult form of the disease, it is an obligation to establish the presence of some toxins of Clostridium difficile in stool samples of patients and/or production of some toxins in liquid culturate of isolates to provide data for the presence of strains which produce only toxin B.